Use of opioids in Latin America: The need of an evidence-based change (2016)
Objective. The subject of this publication has been focused on local considerations for facilitating regional best practice, including identifying and uniformly adopting the most relevant international guidelines on opioid use (OU) in chronic pain management. Design and Setting. The Change Pain Latin America (CPLA) Advisory Panel conducted a comprehensive, robust, and critical analysis of published national and international reviews and guidelines of OU, considering those most appropriate for Latin America. Methods. A PubMed search was conducted using the terms 'opioid,' 'chronic,' and 'pain' and then refined using the filters 'practice guidelines' and 'within the last 5 years' (2007-2012). Once the publications were identified, they were selected using five key criteria: 'Evidence based,' 'Comprehensive,' 'From a well-recognized source,' 'Current publications,' and 'Based on best practice' and then critically analyzed considering 10 key criteria for determining the most relevant guidelines to be applied in Latin America. Results. The initial PubMed search identified 177 reviews and guidelines, which was reduced to 16 articles using the five preliminary criteria. After a secondary analysis according to the 10 key criteria specific to OU in Latin America, 10 publications were selected for critical review and discussion. Conclusions. The CPLA advisory panel considered the 'Safe and effective use of opioids for chronic non-cancer pain' (published in 2010 by the NOUGG of Canada) to be valid, relevant to Latin America, practical, evidence-based, concise, unambiguous, and sufficiently educational to provide clear instruction on OU and pain management and, thus, recommended for uniform adoption across the Latin America region. © 2015 American Academy of Pain Medicine.